(untitled) (The International Journal for Scientific Research, 2026)
This study aimed to examine the impact of risk management dimensions (risk identification, risk assessment, risk response, and risk monitoring) on enhancing the operational safety of ground handling services in Saudi airport support companies. The study adopted a descriptive-analytical approach, targeting a population of (846) employees working in ground support companies at Jeddah, Riyadh, and Madinah airports. A total of (265) valid questionnaires were collected and analyzed using a 28-item instrument based on a five-point Likert scale. The results revealed that both risk management practices and operational safety levels were high. Multiple regression analysis confirmed a statistically significant impact (α ≤ 0.05) of the combined risk management dimensions on operational safety, with a coefficient of determination (R² = 0.661). Risk response ranked first in terms of impact strength, followed by risk monitoring, risk assessment, and risk identification respectively. The study recommended developing specialized training programs in risk response, investing in early warning and electronic monitoring systems, adopting a proactive approach to safety management, and conducting periodic reviews of operational safety policies.